1994
DOI: 10.1029/93ja01501
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism for polar patch formation

Abstract: Polar patches are regions within the polar cap where the F-region electron concentration and airglow emission at 630 nm are enhanced above a background level. Previous observations have demonstrated that polar patches can be readily identified in Polar Anglo-American Conjugate Experiment (PACE) data. Here PACE data and those from complementary instruments are used to show that some polar patches form in the dayside cusp within a few minutes of the simultaneous occurrence of a flow channel event (short-lived pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
187
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(205 citation statements)
references
References 36 publications
16
187
1
1
Order By: Relevance
“…In particular, the concentration of sub-auroral plasma that is convected into the cusp region (Lockwood and Carlson, 1992) may vary and/or the fast ion¯ows that raise the ion temperature may also cause decreases in N e because the loss rates of the plasma are enhanced (Schunk et al, 1975). Rodger et al (1994) suggested these velocity-dependant loss rates may be a signi®cant factor in the cusp/cleft ionosphere. Balmforth et al (1998Balmforth et al ( , 1999 have modelled the e ect of a transient¯ow channel lasting 5 minutes and found results to be consistent with EISCAT observations of a co-located plasma depletion.…”
Section: The Origin Of Plasma Structure In and Between 630 Nm Cusp/clmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the concentration of sub-auroral plasma that is convected into the cusp region (Lockwood and Carlson, 1992) may vary and/or the fast ion¯ows that raise the ion temperature may also cause decreases in N e because the loss rates of the plasma are enhanced (Schunk et al, 1975). Rodger et al (1994) suggested these velocity-dependant loss rates may be a signi®cant factor in the cusp/cleft ionosphere. Balmforth et al (1998Balmforth et al ( , 1999 have modelled the e ect of a transient¯ow channel lasting 5 minutes and found results to be consistent with EISCAT observations of a co-located plasma depletion.…”
Section: The Origin Of Plasma Structure In and Between 630 Nm Cusp/clmentioning
confidence: 99%
“…They interpreted the concentration enhancements as being due to changes in the pattern of¯ow modulating the entry into the polar cap of EUV-produced sub-auroral plasma. However, Rodger et al (1994) pointed out that plasma production by soft particle precipitation and plasma loss by enhanced electric ®elds and reaction rates may also be signi®cant factors in introducing structure into the plasma concentrations on the timescales for¯ux tubes to enter the polar cap.…”
Section: Introductionmentioning
confidence: 99%
“…At high F-region altitudes the lifetime of the plasma is sufficiently long for the ionisation to be drawn through the polar region and into the nightside sector. During its transit through the polar cap the TOI may be modulated into polar patches and various processes have been proposed for this (for example Anderson et al, 1988;Sojka et al, 1993;Rodger et al, 1994;Milan et al, 2002). A modelling study by Bowline et al (1996) indicated that the TOI is expected to be prominent at Ny-Ålesund in the European sector in the evening under conditions of IMF B y negative, and observations of the remnants of the TOI and polar patches on the nightside in this sector are reported by Middleton et al (2008) and Pryse et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, their exact drift direction has to follow the polar ionospheric convection pattern [Rodger et al, 1994]. It is well known that the dawn-dusk component of the IMF (B y ) has a major influence on the orientation of the high-latitude convection pattern when the IMF is southward [Heelis, 1984;Heppner and Maynard, 1987;Greenwald et al, 1990].…”
Section: Introductionmentioning
confidence: 99%